Cardiac Sarcoidosis: Epidemiology, Characteristics, and Outcome Over 25 Years in a Nationwide Study. Issue 7 (17th February 2015) - Kandolin, Riina; Lehtonen, Jukka; Airaksinen, Juhani; Vihinen, Tapani; Miettinen, Heikki; Ylitalo, Kari; Kaikkonen, Kari; Tuohinen, Suvi; Haataja, Petri; Kerola, Tuomas; Kokkonen, Jorma; Pelkonen, Markus; et al.
Abstract : Background—: This study was designed to assess the epidemiology, characteristics, and outcome of cardiac sarcoidosis (CS) in Finland. Methods and Results—: We identified in retrospect all adult (>18 years of age) patients diagnosed with histologically confirmed CS in Finland between 1988 and 2012. A total of 110 patients (71 women) 51±9 years of age (mean±SD) were found and followed up for outcome events to the end of 2013. The annual detection rate of CS increased >20-fold during the 25-year period, reaching 0.31 in 1×10 5 adults between 2008 and 2012. The 2012 prevalence of CS was 2.2 in 1×10 5 . Nearly two thirds of patients had clinically isolated CS. Altogether, 102 of the 110 patients received immunosuppressive therapy, and 56 received an intracardiac defibrillator. Left ventricular function was impaired (ejection fraction <50%) in 65 patients (59%) at diagnosis and showed no overall change over 12 months of steroid therapy. During follow-up (median, 6.6 years), 10 patients died of a cardiac cause, 11 patients underwent transplantation, and another 11 patients suffered an aborted sudden cardiac death. The Kaplan–Meier estimates for 1-, 5-, and 10-year transplantation-free cardiac survival were 97%, 90%, and 83%, respectively. Heart failure at presentation predicted poor outcome (log-rank P =0.0001) with a 10-year transplantation-free cardiac survival of only 53%. Conclusions—: The detection rate of CS has increased markedly in Finland over the last 25 years. With current therapy, the prognosis of CS appears better than generally considered, but patients presenting with heart failure still have poor long-term outcome.